Ice velocity time series, rate of speed change and calving fronts in the Pope, Smith and Kohler region of West Antarctica - Heather Louise Selley; Benjamin J Davison (PANGAEA, 2025)
Ice velocity time series for the Pope, Smith and Kohler basin, Antarctica derived from European Space Agency Copernicus Sentinel-1 satellite data acquired from 2015 to 2022. This dataset consists of annual gridded velocity mosaics provided in GeoTIFF format with a 100 metre by 100 metre grid spacing. The associated spatially and temporally varying error estimate is also provided (see Selley et al., 2025). Also provided are the rate of speed change from 2005-2022 and 2015-2022. The calving front positions of the Crosson and Dotson Ice Shelves from 2005 to 2022. This dataset consisted of two shapefiles. All data is geocoded using a Polar stereographic projection, with a central meridian of 0.0 decimal degrees, and a central latitude of -71.0 decimal degrees. All product units are m/yr.